Setting the course for public space regeneration projects through video acupuncture adapted for architectonic structure façades - Bursiewicz, Natalia (Annales Universitatis Paedagogicae Cracoviensis. Studia de Arte et Educatione, 2022)
The aim of this paper is to examine the role of video acupuncture transferred to architecture in the context of revitalization processes. It provides analyses of this phenomenon and several examples of video acupuncture in different cities. All serve one purpose: The attempt to paint a profound picture of the exceptional potential of this kind of public art in problematic urban areas to induce urban regeneration. Methods used in the research are based on multidisciplinary literature studies. Data is collected from various literature and site observations. This paper will help readers obtain an understanding of how such moving pictures can be beneficial to the revitalization process and how such strategies can revitalize the neighborhoods of the city. The findings of the research show that moving pictures transferred to architecture have a significant impact on the revitalization area thanks to its catalyst transformation potential on people.